When the cure turns toxic: a case report on toxic alkaloids identified by public mass spectral databases - Lei, Yuyan; Yi, Qin; Lu, Junli; Sheng, Yanghao; Xue, Ying (Frontiers in Medicine, 2025)
Aconitine is a highly toxic diterpenoid alkaloid, produced by root of Aconitum brachypodum Diels. (A. brachypodum), also known as “Xue-Shang-Yi-Zhi-Hao,” that is still used in Chinese herbal medicines. Aconitine poisoning remains common in China and other parts of Asia. Cistanche deserticola Y. C. Ma (CD), a drug-food homologue plant, bears a resemblance to A. brachypodum, thus posing a risk of accidental ingestion. Here we present a case report of aconitine poisoning resulting from accidental ingestion. A 54-year-old male presented to the emergency department with toxic symptoms after ingesting homemade herbal medicinal wine. Toxicological analysis was performed, the herbal medicinal wine sample retained from the patient was analyzed using ultrahigh performance liquid chromatography quadrupole-time-of-flight mass spectrometer system. By utilizing the spectral libraries within Global Natural Product Social (GNPS), we identified several aconitum alkaloids—including indaconitine, yunaconitine, talatisamine, and chasmanine—from the herbal medicinal wine sample. This is the first case report of aconitum poisoning where a large-scale public mass spectral databases was used for the rapid screening of toxic substances. The method applied in this study provides a novel approach for the screening of cases involving unexplained poisoning.